Students' perspectives on the use of mobile phone in learning activities - Ibrahim, Norasyikin; Mohd Ayub, Ahmad Fauzi; Md Khambari, Mas Nida (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
This paper discovers descriptive analysis about the relationship between students’ expectancies with the use of mobile phone behavior in academic activity. This study was fully conducted in Universiti Putra Malaysia (UPM) involving 420 of undergraduate students. Three variables of UTAUT model were adapted consist of performance expectancy, effort expectancy and use behavior. From the descriptive analysis, the overall mean of students’ use behavior in adapting mobile phone in academic activity is 4.34 (SD=0.94). For the expectancies analysis, effort expectancies recorded the highest mean 4.06 (SD = 0.80), rather than performance expectancy with the mean 3.89 (SD = 0.77). This result reveals the expectancies are important for student to engage with the use of mobile phone behavior in academic activity.